American Dream in Jay Gatsby as the Main Character of The Great Gatsby Novel - Vidya Muthya Citra (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
Most Americans have dreams for making their life better in the future. The dream can be called American Dream. It exists in all aspects of Americans‟ life, for example a novel. One of the novels that discusses American Dream is The Great Gatsby novel. I write this paper themed American Dream is because I want to analyze the concept of American Dream, the characteristics of it at each character, and the way the main character gets his dream. The method of collecting data that is used in making this paper is the method of descriptive qualitative. Then, the method of approach is sociohistorical method. The theory that is used in making this paper is psychoanalysis theory. In analyzing the American Dream in The Great Gatsby, I found the concept of American Dream that has been existed since 1931 by Adams in his book entitled The Epic of America. Then, the characteristics of American Dream at each character are different from others. The final result is the way the main character trying to get his dream that is not easy to do. Keywords: American dream, The Great Gatsby, Jay Gatsby, descriptive qualitative method, sociohistorical, psychoanalysis theory